Analisis Dampak Keterlambatan Sumber Data dalam Mengajukan Request Notam Ruang Udara di Perum LPPNPI Cabang Palembang - Ananda, Dicky; Sadiatmi, Rini; Wagini, Dini; Oktavia, Alvonsis Renny (Jurnal Bisnis dan Operasi Penerbangan, 2025)
Submitting airspace NOTAM requests is a crucial process in ensuring the safety and efficiency of aviation operations. This process relies on the completeness and timeliness of data provided by various relevant parties. However, delays in receiving the required data often become a significant obstacle, leading to delays in submitting NOTAM requests. This issue can disrupt the smooth flow of flight operations, especially in handling emergencies or significant changes in airspace conditions. This study aims to analyze the impact of delayed data submission on the process at Perum LPPNPI Palembang Branch. Using a qualitative approach with a case study design, data were collected through observation, interviews, and document analysis. The findings reveal that delayed data submission not only hinders the timely submission of requests but also poses potential risks to flight operations and diminishes stakeholder trust.